Concurrence of multiple sclerosis and primary biliary cholangitis: A case series study - Mokhgan Sattar; Maryam Poursadeghfard (Babol University of Medical Sciences, 2020)
Background: Multiple sclerosis (MS) is an autoimmune disorder of the central nervous system which damages the myelin and axon. Primary biliary cholangitis (PBC) is a slow progressive liver disease with autoimmune feature in which non-purulent destructive cholangitis and interlobular bile duct destruction occur. Involvement of each of PBC and MS is thought to be related to environmental exposure in genetically susceptible persons. Case Presentation: Here, we aim to report 3 women 52, 27 and 51 years old with MS and PBC. Conclusion: Although MS seems to have an association with some autoimmune gastrointestinal disorders such as ulcerative colitis, the concurrence of MS and PBC has been rarely reported